INTEGRITY AND CONFLICT RESOLUTION IN NIGERIA: AN ANALYSIS OF TRADE DISPUTES BETWEEN THE FEDERAL GOVERNMENT OF NIGERIA AND THE ACADEMIC STAFF UNION OF UNIVERSITIES, ASUU - Odoziobodo, Severus Ifeanyi (European Scientific Journal, ESJ, 2015)
In so far as man as a being must relate with other human beings on earth, there is bound to be conflict. This is because of man’s inherent tendency to guard his interest at all cost. When one man’s interest clashes with that of his fellow man, conflict ensures. However, for life to continue meaningfully in the face of conflicts of all strands in man’s relationship with one another there is bound to be conflict resolution and reconciliation. But for such resolution and reconciliation to be effective, enduring and sustainable, there is need for integrity on the part of the feuding parties, that is, the quality of being honest and having the strong moral principles to respect agreements. Using the historical analytical method, this paper analyzes the contending issues in ASUU-Federal Government of Nigeria trade disputes, especially the factors that led to the prolonged industrial action embarked upon by the Academic Staff Union of Universities, ASUU which paralyzed academic activities in Nigerian universities for a whole five months in 2013. The paper observes that lack of compliance with the agreements signed by the Federal Government of Nigeria and the Academic Staff of Universities, ASUU led to the 2013 ASUU strike. The paper therefore recommends demonstration of integrity on the part of feuding parties to any conflict as a means to the resolution of the conflict.